PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS X MIA 2 MAN 1 KUANTAN SINGINGI - Karimah, Ahlakul; Solfitri, Titi; Armis, Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to improve the learning process and the student’s mathematical understanding skill by applying Discovery Learning (DL) model. This research is Classroom Action Research with two cycles. This research was conducted in class X science 2 MAN 1 Kuantan Singingi in the second semester of academic year 2017/2018 to 27 students. The required data are qualitative and quantitative data. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Student Activity Sheets) and instruments for collecting data (Observation Sheets and Mathematical-Understanding Tests). Qualitative data were collected by observation technique and analyzed by descriptive narrative analysis. Quantitative data were collected by test technique and analyzed by descriptive statistics analysis. Based on the analysis of the observation sheets showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Result of the test indicates that the student’s learning achievement for the first is 40,4 improved in cycle I to 60,2 and improved to 89.62 in cycle II. The improvement of student’s learning achievement founded for each indicator of mathematical understanding skill: redefine the concept, provide examples and not examples the concept, and applying concepts to solve the problem. This study concludes that the implementation of DL improved the learning process and the student’s mathematical understanding skill at class X science 2 MAN 1 Kuantan Singingi in the second semester of academic year 2017/2018.Key Words: discovery learning, mathematical understanding skill, learning process